P318 RIGHT HEART CHANGE IMPACTS ON SURVIVAL IN PATIENTS AFFECTED BY CARDIAC AMYLOIDOSIS: A SINGLE CENTRE STUDY. (18th May 2022) - Cicco, S; Solimando, A; Susca, N; Inglese, G; Melaccio, A; De Fazio, G; Vacca, A; Ria, R
Abstract: Amyloidosis is due to deposition of an excessive amount of protein in tissues. Cardiac Amyloidosis (CA) is an inauspicious prognostic factor and leading sudden death. We retrospectively analyzed 135 systemic amyloidosis, admitted between 1981 and 2019. 54 patients (46.30% F, aged 63.95±12.82) presented CA at baseline. In 53 patients, it was associated with a multiorgan involvement, while in one there was a primary myocardial deposition. We compared this group with the 81 patients (49.30% F, aged 58.33±15.65) who did not meet criteria for CA. CA presented a decreased SBP (p = 0.036), while nCA had an increased proteinuria (p = 0.02). TnI and NT–proBNP were significantly increased compared to nCA (p = 0.031 and p = 0.047, respectively). In CA patients we found an increased LDH compared to nCA (p = 0.0011). CA patients were also found to have an increased interventricular septum thickness compared to nCA (p = 0.002), a decreased Ejection Fraction (p = 0.0018) and Doppler velocity E/e' ratio (p = 0.0095). Moreover, CA patients had an enhanced right atrium area (p = 0.0179), right ventricle basal diameter (p = 0.0112) and wall thickness (p = 0.0471) compared to nCA, and an increased inferior cava vein diameter (p = 0.0495) as well. TAPSE was the method chosen to evaluate systolic function of the right heart. In CA subjects very poor TAPSE levels were found compared to nCA patients (p = 0.0495). Additionally, we found a significant positive correlation between TAPSE and lymphocyte count (r = 0.47; p = 0.031) as well as Gamma globulins (r = 0.43, p = 0.033), Monoclonal components (r = 0.72; p = 0.047) and IgG values (r = 0.62, p = 0.018). CA patients had very poor survival rates compared to controls (30 vs. 66 months, p = 0.15). Mean survival of CA individuals was worse also when stratified according to NT–proBNP levels, using 2500 pg/mL as class boundary (174 vs. 5.5 months, respectively p = 0.013). In much the same way, a decreased right heart systolic function was correlated with a worse prognosis (18.0 months median survival, not reached in subjects with higher values than 18 mm, p = 0.0186). Finally, our data highlight the potential prognostic and predictive value of right heart alterations characterizing amyloidosis, as a novel clinical parameter correlated to increased LDH and immunoglobulins levels. Overall, we confirm the clinical relevance of cardiac involvement suggests that right heart evaluation may be considered as a new marker for clinical risk stratification in patients with amyloidosis.